Visualization analysis of poisoning-related research based on CiteSpace - Zhu, Wen; Xiao, Yao; Xie, LinShen (Frontiers in Public Health, 2025)
ObjectiveSummarize the current status, hotspots, and frontier trends in poisoning research over the past decade using CiteSpace software, and provide direction for future research in toxicology and public health.MethodsRelevant literature published between 2015 and 2024 was retrieved from the China National Knowledge Infrastructure (CNKI) and Web of Science Core Collection. CiteSpace software was employed to conduct a visual analysis of poisoning-related research literature from the past decade.ResultsA total of 5,644 Chinese articles and 14,985 English articles were included. High-frequency keywords in Chinese literature included “hemoperfusion” and “nursing” while high-frequency keywords in English literature included “exposure” “oxidative stress” and “identification.” Keywords with strong betweenness centrality included “treatment,” “blood purification” and “carbon monoxide.” Recent emerging hotspots in Chinese literature were “liver function” and “oxidative stress” while in English literature, “gut microbiota” has recently gained attention.ConclusionPoisoning-related research has shown an overall upward trend. The research hotspots in this field primarily include epidemiology, oxidative stress, clinical treatment, prognosis, and chemical substances (e.g., CO, paraquat). In-depth studies on gut microbiota and oxidative stress are expected to become future research trends in this field.